PERLINDUNGAN HUKUM TERHADAP ETNIS ROHINGYA DALAM PERPEKTIF HAK ASASI MANUSIA - Periani, Aniek; Hariadi, Wahyu (Universitas Pendidikan Ganesha, 2020)
Human rights are basic rights that humans have from the time they were born or when they began to interact with society. This right cannot be taken by anyone, even the state has the responsibility to protect the rights possessed by each individual, regardless of whether he is an individual belonging to the ethnic majority or ethnic minority. Regarding ethnic minorities, there is already protection for ethnic minorities regarding their rights which under international law are generally regulated in international instruments, Rohingyas in Myanmar are ethnic minorities who experience many violations such as the termination of citizenship, restriction of freedom of confession religion, oppression of children and women. Some instruments that regulate violations experienced by the Rohingya ethnic group are the Universal Declaration of Human Rights, the Declaration on the Rights of Population which includes Minority Groups Based on Citizenship.Â